Synthesis, Dehydroxylation and Sintering of Porous Mg(OH)2-MgO Clusters: Evolution of Microstructure and Physical Properties - Salomão, Rafael; Arruda, C. C.; Antunes, Maria L.P. [UNESP] (Springer Nature, 2020)
Abstract: Magnesium hydroxide (Mg(OH)2 or brucite) and magnesium oxide (MgO or magnesia) are essential raw materials for many industrial applications. Several studies have explored their production methods and the changes in their properties caused by adjustments in synthesis and calcination conditions. However, the ways the particles' microstructure changes along a full thermal treatment up to sintering remain unclear. This study investigated the effects of thermal treatments (120-1500 °C) on the physical properties and microstructure of clusters of Mg(OH)2 nanoparticles prepared by soluble-Mg-salt precipitation assisted by a surfactant agent.